The Influence of Pyridoxin in the Theatment of Tetanus Neonatorum - Dianto Dianto; Immanuel Mustadjab (Paediatrica Indonesiana, 1991)
During a 2-year-period (1988-1990) 31 patients with tetanus neonatorum were recruited for this study. The patients were divided into 2 groups: The first group (15 patients) was treated with ATS injection, oral metronidazole and amoxycillin, and diazepam suppositoria. The second group (16 patients) was treated with the same regimen, as the first group plus pyridoxin injection 100 mg on the first day followed by 25 mg orally on the next days. There was no statistical difference in the two groups concerning the gestation period, sex, severity of the disease (p> 0.05), place of delivery (all at home) and mode of delivery delivered by traditional (midwife/dukun). The mortality of the first group (without pyridoxin) was 60% and the second (with pyridoxin) 37.5% (p < 0.05).